2020
DOI: 10.1021/acs.oprd.9b00515
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into an Unexpected Impurity: A Practical Approach to Process Development for the Addition of Grignard Reagents to Aldehydes Using Continuous Flow Synthesis

Abstract: This work presents a case study of process development using continuous flow synthesis. In developing a process for manufacturing drug substances in batch reactors, we unexpectedly obtained a significant amount of a trimerized byproduct on addition of MeMgBr to an aldehyde. Consideration of a plausible generation mechanism for the byproduct indicated that it arose from a reaction between the starting material and the Mg salt of the target product. This led us to try applying continuous flow synthesis to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…It was also anticipated that any decrease in the mixing efficiency due to the widening of the inner diameter would be compensated for by increasing the flow rate 16 times. 22 Although the isolated yield of 71% was somewhat lower than desired, it was noted that some cavitation occurred in the pumps during operation, which would have caused imprecise flow rates and decreased yields. It was estimated that cavitation prevented ca.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…It was also anticipated that any decrease in the mixing efficiency due to the widening of the inner diameter would be compensated for by increasing the flow rate 16 times. 22 Although the isolated yield of 71% was somewhat lower than desired, it was noted that some cavitation occurred in the pumps during operation, which would have caused imprecise flow rates and decreased yields. It was estimated that cavitation prevented ca.…”
Section: Resultsmentioning
confidence: 97%
“…By increasing the inside diameter of the micromixer to 1.0 mm for scale-up, it was thought that the risk of clogging would be reduced. It was also anticipated that any decrease in the mixing efficiency due to the widening of the inner diameter would be compensated for by increasing the flow rate 16 times . Although the isolated yield of 71% was somewhat lower than desired, it was noted that some cavitation occurred in the pumps during operation, which would have caused imprecise flow rates and decreased yields.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize the reason for the low accuracy in entry 1 to be as follows. In this reaction, Oppenauer oxidation of the Mg salt of 2 with 1 was observed, 14 which indicated that 1 interacted with the Mg salt of 2 in situ. When the conversion was less than 50%, the starting material 1 was more than the Mg salt of 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In our previous work, we developed a Grignard reaction under continuous flow conditions, in which the addition of MeMgBr to methyl 4-formyl benzoate ( 1 ) gave up to 98% yield of the target product 2 . This flow system succeeded in suppressing an unexpected trimerized byproduct 3 due to fast mixing.…”
Section: Introductionmentioning
confidence: 99%
“…As an emerging and promising technique, flow chemistry shows considerable advantages over traditional chemical processes and has been applied to address long-standing challenges in the field of organic synthesis and pharmaceutical synthesis . Compared with the batch process, the continuous flow process involving Grignard reagents generally improves yields or selectivities at mild conditions, and the rapid and reliable scale-up is also permitted . With our interest in the efficient synthesis of enantioenriched piperidines, herein, we report an operationally simple continuous flow protocol using readily accessible δ-bromo N -( tert -butylsulfinyl)­imine and Grignard reagents under mild conditions, leading to a diverse range of functionalized α-substituted piperidines within minutes (Scheme b).…”
mentioning
confidence: 99%